Enhancing the searchability of page-image PDF documents using an aligned hidden layer from a truth text - Knight, Ian A.; Brailsford, David F. (2016)
The search accuracy achieved in a PDF image-plus-hidden- text (PDF-IT) document depends upon the accuracy of the optical character recognition (OCR) process that produced the searchable hidden text layer. In many cases recognising words in a blurred area of a PDF page image may exceed the capabilities of an OCR engine. This paper describes a project to replace an inadequate hidden textual layer of a PDF-IT file with a more accurate hidden layer produced from a `truth text'. The alignment of the truth text with the image is guided by using OCR- provided page-image co-ordinates, for those glyphs that are correctly recognised, as a set of fixed location points between which other truth-text words can be inserted and aligned with blurred glyphs in the image. Results are presented to show the much enhanced searchability of this new file when compared to that of the original file, which had an OCR-produced hidden layer with no truth-text enhancement.